(untitled) - Straub, Peter (New York, 2004)
Willy Patrick, the author of the Caldecott-winning young-adult novel In the Night Room, thinks she is loosing her mind again. Two weeks before her second marriage, on her way home one day, Willy is drawn into the parking lot of a warehouse. Knowing that her daughter Holly is being held in that building, she wants to rescue her. But what she knows is impossible, for her daughter is dead. On the same day, author Timothy Underhill, struggling with a new book about a troubled young woman, is confronted with the ghost of his nine-year-old sister, April. Soon after, Underhill begins to receive eerie, fragmented e-mails that he finally realizes are from dead people whom he knew in his youth. Like his sister, they want to tell him something. When Willy and Timothy meet, they recognize each other, realizing that they must join forces to confront the evils surrounding them.
Keywords: English language,Ngôn ngữ Anh; Study and teaching,Học và dạy